Maternal gut microbiota influences immune activation at the maternal-fetal interface affecting pregnancy outcome - Silvia Giugliano; Andrea Gatti; Martina Rusin; Tilo Schorn; Silvia Pimazzoni; Michela Calanni-Pileri; Valentina Fraccascia; Sara Carloni; Maria Rescigno (Nature Communications)
Abstract Preeclampsia is a leading cause of morbidity and mortality in pregnant women, affecting 5–8% of gestations worldwide. Its development is influenced by maternal immune abnormalities, metabolic disorders, and gut dysbiosis. In this study, we show that gut dysbiosis in pregnant C57BL/6J dams leads to increased fetal resorption, impaired placental development and altered vascularization. These adverse outcomes are associated with key pathological features of preeclampsia, including hypoxia, endoplasmic reticulum (ER) stress and reduction in uterine natural killer (NK) cell numbers. Furthermore, gut dysbiosis significantly perturbs placental carbohydrate metabolism, which impairs NK cell IFN-γ secretion. Notably, glucose supplementation restores placental NK cell function and reduces fetal resorption, suggesting that the observed impairment is reversible and dependent on a lower glycolytic rate. These findings highlight maternal gut microbiota as a key player in carbohydrate metabolism, with a pivotal role in modulating placental immunity and pregnancy outcome. The results provide valuable insights into potential metabolic biomarkers and suggest that targeting the gut microbiota may offer a strategy for preventing preeclampsia.